Penyisihan Krom Dalam Limbah Cair Laboratorium Dengan Metode Adsorpsi dan Fitoremediasi - Titik Indrawati; Nunung Isnaini Dwi Ningsih; Padya Sumarwanto (UPT Laboratorium Terpadu, Universitas Diponegoro, 2023)
The laboratory is one of the units that produce liquid waste which in addition to having infectious properties is also toxic, which if not managed properly will have the potential to damage the ernvironment and living things. Laboratory wastewater treatment is important because the treament and procurement of WWTPs that meet the requirements are very high cost, therefore it is neceessary to do research to find a simple but effective liquid waste treatment technology to reduce the level of liquid waste parameters, easy to make, using local materials, and the price is affordable. This study aims to determine the performance of sandston/gravel media, fly ash, vetiver (Vetiveria Zizanoides L), and the third mixture in reducing chromium content in laboratory wastewater by applying adsorption and phytoremediatioon methods. The liquid waste used is artificial waste made of Potassium Dichromate with a concentration of 15 mg/L. This research was conducted on a laboratory scale, using beaker. Adsorption experiments were carried out on fly ash and gravel media with weight variations of 20 g (2% w/v), 30 g (3% w/v) and 50 g (5% w/v). Phytoremediation experiments were carried out on vetiver (Vetiveria Zizanoides L) with variations in plant weight, namely 70 g (2% w/v), 170 g (3% w/v) and 200 g (5% w/v), while fro adsorption experiments the mixture of gravel and fly ash was carried our with variatons in weight of 40 g (2% w/v), 60 g (3% w/v) and 100 g (5% w/v) with ration of 1:1, respectively. The mixture of gravel, fly ash and plants was carried out in a ratio of 1:1:1 with a weight of 100 g each. Observations were made on chromium levels on day 1 and 15. The results showed that the removal of chromium levels in each adsorption experiment using gravel was an average of 0,32 mg/L, whilae adsorption using fly ash average 1.58 mg/L; 10.135 for fly ash; 2.00% for gravel, and 24.16% for vetiver. The decrease ini chromium levels with vetiver plants was 3,78 mg/L on average. The highest removal efficiency (RE) value of 76.64% occured in the adsorption and phytoremediation experiments using vetiver plants and a mixture of fly ash and gravel media a ratio (1:1:1) with each weight of 100 g (5% w/v).